Quality of the Indoor Environment in Elderly Care Centers in Two Cities in Central Portugal: Viseu and Covilhã - Pinto, Manuel (2019)
Assessments of Indoor Environment Quality (IEQ) present a very significant challenge when analyses are undertaken mainly in buildings that include a particularly sensitive and vulnerable population, such as elderly people. In order to maintain an indoor environment that is adequate for occupants, it is necessary to comply with a set of requirements (for TVOC, the Portuguese threshold values) regarding concentrations of airborne pollutants and hygrothermal comfort conditions. This paper studies IEQ in compartments in 3 buildings in two cities in central Portugal, Viseu and Covilhã, which hold elderly care centers. The following environmental parameters were continuously recorded: air temperature, relative humidity, concentration of carbon dioxide, formaldehyde, and total volatile organic compounds and ventilation rates. An analysis of the obtained results was performed, taking recommended guidelines and threshold values into account, thus making it possible to evaluate the IEQ conditions and hygrothermal comfort in the selected indoor spaces. On the basis of the conclusions reached and the observed problems of hygrothermal comfort and indoor pollutants in the indoor spaces, a number of recommendations are proposed, specifically in terms of climate control, ventilation, and maintenance, in order to obtain an overall improvement of IEQ.